Magnetofection is superior to other chemical transfection methods in a microglial cell line - Smolders, Silke; Kessels, Sofie; Smolders, Sophie Marie-Thérèse; Poulhes, Florent; Zelphati, Olivier; Sapet, Cedric; Brône, Bert (Journal of neuroscience methods, 2018)
•Glial-Mag magnetofection is a novel method for transfection optimized for phagocytic BV2 cells.•Compared to other chemical transfection methods, Glial-Mag magnetofection yields a high transfection efficiency.•Efficient transfection leads to a short-lived activation of BV2 cells that ceases within 48h. Microglia, the resident phagocytic cells of the brain, have recently been the subject of intense investigation given their role in pathology and normal brain physiology. In general, phagocytic cells are hard to transfect with plasmid DNA. The BV2 cell line is a murine cell line of microglial origin which is often used to study this cell type in vitro. Unfortunately, this microglial cell line is, like other phagocytic cells, resistant to transfection. Magnetofection is a well-established transfection method that combines DNA with magnetic particles which, under the influence of a magnetic field, ensures a high concentration of particles in proximity of cultured cells. Only recently, Glial-Mag was specifically developed for efficient transfection of microglia and microglial cell lines. Magnetofection with Glial-Mag yielded a transfection efficiency of 34.95% in BV2 cells, 24h after transfection with an eGFP-expressing plasmid. Efficient gene delivery caused a modest and short-lived cell activation (as measured by IL6 secretion) that ceased by 24h after transfection. Here we show that Glial-Mag magnetofection of BV2 cells yielded a significantly higher transfection efficiency (34.95%) compared to other chemical transfection methods including calcium-phoshate precipication (0.34%), X-tremeGENE (3.30%) and Lipofectamine 2000 (12.51%). Transfection of BV2 cells using Glial-Mag magnetofection is superior compared to other chemical transfection methods and could be considered as the method of choice to chemically transfect microglial cell lines.